Nature cures, give cannabis a chance a campaign on the acceptance of medical marijuana in the philippines - Ruga, Paola Beatrice L.
Marijuana, also known as cannabis, is considered one of the most commonly abused drugs and is categorized as a dangerous drug. However, according to several studies, the marijuana has several medical benefits. Many countries have acknowledged these benefits and have changed their perceptions on the drug. Furthermore, some of these countries have also not only the medical use, but also the recreational use of marijuana. In the Philippines, marijuana is still banned even for medical use. A bill was proposed by Hon. Rodolfo T. Albano, House Bill 180 Philippine Medical Cannabis Act, which sought to legalize medical cannabis or to give patients with debilitating diseases access to the drug. Although the bill is still undergoing the legislation process, there are those who do not agree, even lawmakers. The question now, is why? Such as this will be discussed in the study.